P167 VEDOLIZUMAB TROUGH LEVELS AND ANTIBODIES IN INFLAMMATORY BOWEL DISEASE: UPDATED INITIAL EXPERIENCE. (18th January 2018) - Al-Bawardy, Badr; Ramos, Guilherme Piovezani; Willrich, Maria Alice V; Park, Sang; Raffals, Laura; Tremaine, William J; Loftus, Edward V
Abstract: Background/Aims: The utility of vedolizumab (VDZ) trough levels (VTL) in the management of patients with inflammatory bowel disease (IBD) has not been well defined. The aims of this study are to determine: the median VTL and frequency of antibodies, the correlation of VTL with C-reactive protein (CRP) and mucosal healing (MH), and change in clinical management based on VTL. Methods: A retrospective study of IBD patients on VDZ with levels checked from January 2008-March 2017 was conducted. The VTL was checked before week 14 (n=8) and during maintenance (n=99). Outcomes included: median VTL; presence of anti-VDZ antibodies; effect of corticosteroids (CS) and immunomodulator (IMM) therapy on VTL; and median VTL associated with normal CRP (< 3 mg/dL) and MH. Results: A total of 107 patients (62% CD, 29% UC, 6% indeterminate colitis, 3% pouchitis) were included in the study (Table 1). VDZ was administered every 8 weeks (n=74), 6 weeks (n=10) and 4 weeks (n=22). The median VTL was 15.9 (0–58) ug/mL and was higher in the 4 week group compared to the 6 and 8 week groups (25.5 vs. 16.8 vs. 13.9 ug/mL; p=0.002). Only one patient (0.9%) had a detectable antibody level (> 500 ug/mL). Median VTL was similar in patients on and off CS (17.3 vs. 15.8; p=0.74) and in patients with and without IMM (14.6 vs. 16.1; p=0.40). Median VTL was 13.7 ug/mL and 15.9 ug/mL in patients with and without MH, respectively (p=0.91). Patients with a normal CRP had a median VTL of 17.3 ug/mL compared to 14.8 ug/mL in those with high CRP (p=0.80). VTL resulted in change in clinical management in 71%: decrease in dose interval (n=59), addition of an IMM (n=4) and discontinuation of VDZ (n=13). Conclusions: In this cohort, the rate of developing VDZ antibodies was < 1%. Shorter dose intervals resulted in higher VTL, while concomitant CS and IMM therapy did not affect levels. No correlation between VTL with MH and CRP was detected. Our results are limited by single center, retrospective study design.